The art of social engineering : a comprehensive guide to uncovering the secrets behind the human dynamics in cybersecurity /: a comprehensive guide to uncovering the secrets behind the human dynamics in cybersecurity. (2023) - (Cybersecurity expert), Bravo, Cesar; Toska, Desilda
No abstract available